Hak atas Akses yang Adil terhadap Pendidikan Tinggi: Analisis Berdasarkan Falsafah Pancasila - Lubis, Rahmad; Purnama, Desi; Sulaiman, Heri (SIGn Jurnal Hukum, 2024)
This research aims to comprehensively analyze citizens’ right to equitable access to higher education in Indonesia based on Pancasila’s philosophy. Employing a normative legal research methodology, this study examines the issue through statute and conceptual approaches. Data were analyzed using qualitative content analysis techniques to describe and address the research problem in depth. The findings indicate that equitable access to higher education is a constitutional right of every Indonesian citizen guaranteed by Pancasila and the 1945 Constitution. As an embodiment of the welfare state principle, the state is obliged to create a just, equitable, quality, and affordable higher education system for all levels of society. It requires affirmative regulations, innovative and equitable financing schemes, and a reliable quality assurance system. Higher education must be seen as a strategic instrument to break the cycle of structural poverty, enhance social mobility, and realize distributive justice by prioritizing the principle of social solidarity. Therefore, the projection towards free higher education, especially in state universities, is a strategic step that needs to be realized gradually and sustainably, supported by progressive tax system reform, increased allocation of education budgets, and optimization of alternative funding sources, as a form of progressive interpretation of Article 31 section (1) of the 1945 Constitution.